Clinical profile of transfusion-dependent thalassemia major children with reference to serum ferritin and liver function: A prospective observational study - Chiluka Sudhakar; Blessy Prabhu Priyanka S; Shanmuga Sundaram M; Rajashekar K (Asian Journal of Medical Sciences, 2023)
Background: Thalassemia major is a genetic disorder characterized by severe anemia and the need for lifelong blood transfusions. Aims and Objectives: The aim of this study was to investigate the clinical profile of transfusion-dependent thalassemia major children with reference to serum ferritin levels and liver function. Materials and Methods: A prospective observational study included 100 children aged 1–12 years with beta-thalassemia major, who were receiving blood transfusions. Clinical data, including growth parameters, serum ferritin levels, and liver function tests, were collected. Descriptive and inferential statistical analyses were performed. Results: The study population predominantly consisted of children aged 1–5 years (54%) and males (51%). Hindu children accounted for 85% of the participants. Most children were diagnosed with thalassemia major before the age of 1 year (84%) and were diagnosed through Hb electrophoresis (77%). The majority of children received blood transfusions every 15–30 days (49%). Pre-transfusion hemoglobin levels ranged from <5 g/dL to 8.0 g/dL, while post-transfusion levels ranged from 7.1 g/dL to 10.1 g/dL. Liver function tests indicated the mean values for total serum bilirubin (0.81±0.2), direct bilirubin (0.34±0.10), indirect bilirubin (0.49±0.10), aspartate transaminase (47.22±11.06), alanine transaminase (45.45±8.97), alkaline phosphatase (97.74±4.39), total proteins (6.28±0.29), and serum albumin (3.72±0.2). No significant changes were observed in growth parameters over the 18-month study period. Conclusion: This study provides insights into the clinical profile of children with transfusion-dependent thalassemia major, emphasizing the significance of early diagnosis, regular transfusions, and monitoring of serum ferritin levels and liver function.